Encapsulation and sustained release of curcumin by a composite hydrogel of lotus root amylopectin and chitosan. (15th March 2020) - Liu, Kang; Huang, Rui-Lin; Zha, Xue-Qiang; Li, Qiang-Ming; Pan, Li-Hua; Luo, Jian-Ping
Graphical abstract: Highlights: Lotus root amylopectin-chitosan composite hydrogel was prepared. Curcumin was successfully encapsulated in the composite hydrogel. Stability of curcumin was improved by the composite hydrogel encapsulation. Bioavailability of curcumin was increased by the composite hydrogel encapsulation. Abstract: In the present work, lotus root amylopectin (LRA)-chitosan (CS) composite hydrogel was developed as a delivery system for curcumin (CUR). Results exhibited that a stable LRA-CS-CUR hydrogel was formed using LRA and CS in the ratio of 3:2 (w/w) at pH 4.0. Under this condition, the particle size, polydispersity index and zeta potential of the LRA-CS-CUR was 410.3 nm, 0.211 and +26.47 mV, respectively. The analysis of transmission electron microscopy, fourier transform infrared spectroscopy and X-ray diffractometer revealed that curcumin was successfully encapsulated in the LRA-CS hydrogel, giving a high encapsulation efficiency of 90.3 %. Moreover, this composite hydrogel could significantly improve the solubility and stability of curcumin. The release characteristics of encapsulated curcumin in simulated gastric fluid and simulated intestinal fluid were further investigated. Results exhibited that the LRA-CS hydrogel enabled curcumin to be stable in stomach and release in small intestine.